A Facile Access to Fluorinated Pyrrolidines via Catalytic Asymmetric 1,3-Dipolar Cycloaddition of Azomethine Ylides with Methyl a-Fluoroacrylate - 严定策 李清华 王春江 (Chinese journal of chemistry, 2012)
Asymmetric 1,3-dipolar cycloaddition of methyl a-fluoroacrylate with azomethine ylides for the construction of optically active fluorinated pyrrolidines bearing one unique fluorinated quaternary and two tertiary stereogenic cen- ters has been achieved with Cu（CH3CN）4BF4/TF-BiphamPhos complexes for the first time. This catalytic system performs well over a broad scope of substrates, providing the synthetically useful adducts in good yields and excel- lent diastereoselectivities and good to high enantioselectivities.